Formal Risk Adjustment by Private Employers - Randall P. Ellis (SAGE Publishing, 2001)
This paper explores explanations for why few private employers have adopted formal risk adjustment. The lack of data, challenges of using highly imperfect signals, and absence of market power are not compelling explanations. Alternative strategies that reduce selection problems are clearly important. The central argument is that U.S. health markets are not in equilibrium, but rather are changing rapidly. Since many agents-consumers, employers, health plans, and providers-do not currently demand formal risk adjustment, it is not surprising that adoption has been slow. Recent changes in health plan markets may change the demand and accelerate future adoption.